Oxycodone Self-Administration Induces Alterations in Expression of Integrin, Semaphorin and Ephrin Genes in the Mouse Striatum - Yuferov, Vadim; Zhang, Yong; Liang, Yupu; Zhao, Connie; Randesi, Matthew; Kreek, Mary J. (Frontiers in Psychiatry, 2018)
Oxycodone is one a commonly used medication for pain, and is also a widely abused prescription opioid, like other short-acting MOPr agonists. Neurochemical and structural adaptations in brain following chronic MOPr-agonist administration are thought to underlie pathogenesis and persistence of opiate addiction. Many axon guidance molecules, such as integrins, semaphorins, and ephrins may contribute to oxycodone-induced neuroadaptations through alterations in axon-target connections and synaptogenesis, that may be implicated in the behaviors associated with opiate addiction. However, little is known about this important area. The aim of this study is to investigate alterations in expression of selected integrin, semaphorin, ephrins, netrin, and slit genes in the nucleus accumbens (NAc) and caudate putamen (CPu) of mice following extended 14-day oxycodone self-administration (SA), using RNAseq. Methods: Total RNA from the NAc and CPu were isolated from adult male C57BL/6J mice within 1 h after the last session of oxycodone in a 14-day self-administration paradigm (4h/day, 0.25 mg/kg/infusion, FR1) or from yoked saline controls. Gene expressions were examined using RNA sequencing (RNA-Seq) technology. RNA-Seq libraries were prepared using Illumina's TruSeq® Stranded Total RNA LT kit. The reads were aligned to the mouse reference genome (version mm10) using STAR. DESeq2 was applied to the counts of protein coding genes to estimate the fold change between the treatment groups. False Discovery Rate (FDR) q < 0.1 were used to select genes that have a significant expression change. For selection of a subset of genes related to axon guidance pathway, REACTOME was used. Results: Among 38 known genes of the integrin, semaphorin, and ephrin gene families, RNA-seq data revealed up-regulation of six genes in the NAc: heterodimer receptor, integrins Itgal, Itgb2, and Itgam, and its ligand semaphorin Sema7a, two semaphorin receptors, plexins Plxnd1 and Plxdc1. There was down-regulation of eight genes in this region: two integrin genes Itga3 and Itgb8, semaphorins Sema3c, Sema4g, Sema6a, Sema6d, semaphorin receptor neuropilin Nrp2, and ephrin receptor Epha3. In the CPu, there were five differentially expressed axon guidance genes: up-regulation of three integrin genes, Itgal, Itgb2, Itga1, and down-regulation of Itga9 and ephrin Efna3 were thus observed. No significant alterations in expression of Netrin-1 or Slit were observed. Conclusion: We provide evidence for alterations in the expression of selective axon guidance genes in adult mouse brain following chronic self-administration of oxycodone. Further examination of oxycodone-induced changes in the expression of these specific axon guidance molecules and integrin genes in relation to behavior may provide new insights into development of addiction to oxycodone.